3D Vision Improves Outcomes in Early Cervical Cancer Treated with Laparoscopic Type B Radical Hysterectomy and Pelvic Lymphadenectomy. Issue 1 (January 2017) - Raspagliesi, Francesco; Bogani, Giorgio; Martinelli, Fabio; Signorelli, Mauro; Scaffa, Cono; Sabatucci, Ilaria; Lorusso, Domenica; Ditto, Antonino
Purpose: To evaluate the alterations on surgical outcomes after of the implementation of 3D laparoscopic technology for the surgical treatment of early-stage cervical carcinoma. Methods: Data of patients undergoing type B radical hysterectomy (with or without bilateral salpingo-oophorectomy) and pelvic lymphadenectomy via 3D laparoscopy were compared with a historical cohort of patients undergoing type B radical hysterectomy via conventional laparoscopy. Complications (within 60 days) were graded per the Accordion severity system. Results: Data of 75 patients were studied: 15 (20%) and 60 (80%) patients undergoing surgery via 3D laparoscopy and conventional laparoscopy, respectively. Baseline patient characteristics as well as pathologic findings were similar between groups (p>0.1). Patients undergoing 3D laparoscopy experienced a trend toward shorter operative time than patients undergoing conventional laparoscopy (176.7 ± 74.6 vs 215.9 ± 61.6 minutes; p = 0.09). Similarly, patients undergoing 3D laparoscopic radical hysterectomy experienced shorter length of hospital stay (2 days, range 2-6, vs 4 days, range 3-11; p<0.001) in comparison to patients in the control group, while no difference in estimated blood loss was observed (p = 0.88). No between-group difference in complication rate was observed. Conclusions: 3D technology is a safe and effective way to perform type B radical hysterectomy and pelvic node dissection in early-stage cervical cancer. Further large prospective studies are warranted in order to assess the cost-effectiveness of the introduction of 3D technology in comparison to robotic assisted surgery.